Water productivity in context: the experiences of Taiwan and the Philippines over the past half-century - Barker, Randolph; Levine, G. (International Water Management Institute, 2012)
As we enter an era of increasing water scarcity, there is a growing interest to find ways to capture and put water to more productive uses. Substantial increases in the productivity of water in agriculture are needed to meet the demands for food and ensure environmental security, and to satisfy the demands for non-agricultural uses. However, increasing water productivity in rice-dominated agriculture is a function of the irrigation infrastructure, advances in rice-plant breeding, and the physical, institutional and socioeconomic environments. This paper first describes the potential ways in which increased water productivity can be achieved in the context of rice production in Asia. It then illustrates the ways in which the differences in the environmental context affect the ability to increase water productivity, the approaches used and the incentives to do so. This is explained using two ?case studies? reflecting the experiences of Taiwan and the Philippines over the past half-century.